2015
DOI: 10.18544/ep-01.14.04.1626
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin concentrations in adolescents and young adults with growth hormone deficiency

Abstract: Introduction. Leptin (LEP) is the first from described adipokines of pleiotropic action. Growth hormone deficiency (GHD) may contribute to the development of disturbances in the functioning of adipose tissue (AT), and many disorders observed in untreated patients with GHD coincides with the spectrum of action of leptin. Results of published papers according the effects of GH secretion on LEP are divergent. There is no data on serum LEP in a group of adolescents and young adults with varying degrees of GHD in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Its endocrine function could be partially modulated by the GH/ IGF-1 axis and adipokines derived from adipose tissue possibly mediate some metabolic actions of GH, such as the influence on energy balance and glucose and lipid metabolism (Kershaw et al, 2004;Trayhurn et al, 2006;Berryman et al, 2011;Meazza et al, 2014;Ciresi et al, 2016;Rothermel et al, 2016;Berryman et al, 2017). Several studies indicate that in patients with GHD, both children and adults, the adipokine profile could be impaired, and GH replacement therapy could be beneficial, but the reported results are discordant (Ciresi et al, 2007;Nozue et al, 2007;Andersson et al, 2009;Ciresi et al, 2016;Oświęcimska et al, 2017;Stawerska et al, 2017). Concentrations of adiponectin seem to be unaffected in children with untreated GHD (Ciresi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its endocrine function could be partially modulated by the GH/ IGF-1 axis and adipokines derived from adipose tissue possibly mediate some metabolic actions of GH, such as the influence on energy balance and glucose and lipid metabolism (Kershaw et al, 2004;Trayhurn et al, 2006;Berryman et al, 2011;Meazza et al, 2014;Ciresi et al, 2016;Rothermel et al, 2016;Berryman et al, 2017). Several studies indicate that in patients with GHD, both children and adults, the adipokine profile could be impaired, and GH replacement therapy could be beneficial, but the reported results are discordant (Ciresi et al, 2007;Nozue et al, 2007;Andersson et al, 2009;Ciresi et al, 2016;Oświęcimska et al, 2017;Stawerska et al, 2017). Concentrations of adiponectin seem to be unaffected in children with untreated GHD (Ciresi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in the results of different studies evaluating the adipokine profile in untreated patients with GHD could be a result of varied metabolic panel reported in those children by several authors, who indicate that not all children with GHD have an impaired metabolic profile (Gleeson et al, 2007;López-Siguero et al, 2011;Meazza et al, 2014;Ciresi et al, 2016;Stawerska et al, 2017). Data concerning chang-es in the lipid profile, glucose homeostasis and thyroid function were also divergent (van der Sluis et al, 2002;Andersson et al, 2009;Smyczyńska et al, 2010;López-Siguero et al, 2011;Ciresi et al, 2016;Giavoli et al, 2017;Oświęcimska et al, 2017;Stawerska et al, 2017). The study by Stawerska et al (2017) confirmed that the baseline metabolic profile in GH-deficient children was not homogenous, and was better in GHdeficient children with low IGF-1 bioavailability expressed as the insulin-like growth factor-1/insulin-like growth factor binding protein-3 (IGF-1/IGFBP-3) molar ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Among many of them, leptin, adiponectin, resistin, visfatin, and others are mentioned [3]. Interestingly, previous studies on adipokines have focused mainly on aspects related to diabetes, obesity, metabolic syndrome, cardiomyopathy, anorexia nervosa, eating disorders, or tendency for atherogenesis [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have confirmed close relationships between reduced birth size parameters and long-term risk for overweight and obesity, insulin resistance, type 2 diabetes, hypertension and cardiovascular disease in adulthood (Forsén et al, 2000;Ong et al, 2000;Eriksson et al, 2002). Although the exact mechanisms regulating the relationships between birth size and growth in childhood are not well described, the influence of adipokines and hormones, as well as a number of growth factors, are also postulated (Bozzola et al, 2010;Oświęcimska et al, 2017;Renes et al, 2019). Several changes in carbohydrate and lipid metabolism occurring after the initiation of rhGH therapy in GH-deficient children are related mainly to the action of the GH/IGF-I axis itself and, especially in adolescents, to the influence of sex steroids (Møller & Jørgensen, 2009;Rothermel & Reinehr, 2016;Stawerska et al, 2017;Witkowska-Sędek et al, 2018).…”
Section: Discussionmentioning
confidence: 98%